Radiolabelling and preliminary evaluation of 68Ga-tetrapyrrole derivatives as potential tracers for PET - Zoller, Frederic (Nuclear medicine and biology, 2013)
Tetrapyrroles are multisided natural products which are of relevance in clinical medicine. Owing to their specific accumulation in tumour tissue, porp…